A framework for comparative performance study on virtualised machines. (21st November 2014) - Zhao, Jiaqi; Tao, Jie; Fürlinger, Karl
The virtualisation technology has been widely used today in various research fields, including high performance computing, grid computing, cloud computing as well as server–client systems. The virtualisation introduces advantages such as on–demand customised resource provision, easy management and support for multiple Operating Systems, etc. However, this technology also results in a performance loss due to the additional virtualisation layer. To help application developers study the performance issues on virtualised multicore machines, we developed a tool framework with a set of performance tools that collect the runtime performance data and demonstrate the different runtime application behaviour on both the physical machine and the virtual machine within a single view. We applied the tool framework to analyse a number of benchmark applications and conducted optimisations based on the analysis discovery. The initial experimental results show a significant performance gain.